Metaethical Model of Moral Research: Semantic and Epistemological Aspects - Patapas, Aleksandras (Problemos, 2001)
An attempt is made to review the beginnings of metaethical discourse. Moore’s theory is considered as a key for the reconstruction of metaethical model of moral research. This new strategy of moral research was primarily based on reflection of essentially casuistic status of previous moral investigations which by and large were based on connotative definitions of ethical terms. An alternative denotative of definition of moral terms is considered as the new strategy of defining moral concepts. Finally, the problem of moral obligation is identified as a focal point of metaethical model of moral research. Epistemological significance of Moore's proposed principle of “organic unity” as a core of analysis of moral obligation is pointed out and discussed.
Keywords: metaethical model; moral duty; organic unity